Incidental Findings on FDG PET/CT in Head and Neck Cancer. (March 2018) - Britt, Christopher J.; Maas, Austin M.; Kennedy, Tabassum A.; Hartig, Gregory K.
Objective: 18F-fluoro-deoxy-glucose positron emission tomography/computed tomography (FDG PET/CT) imaging is common in head and neck cancer and often identifies incidental findings that necessitate additional patient evaluations. Our goal was to assess the frequency and nature of these incidental imaging findings on FDG-PET/CT. Study Design: Retrospective cohort study. Setting: Tertiary medical center. Subjects and Methods: All patients with head and neck cancer who had undergone FDG-PET/CT imaging between January 2014 and June 2015 at our institution were evaluated for incidental findings. Results: A total of 293 patients met criteria; more than one-third (n = 103) had at least 1 finding unrelated to their head and neck cancer, for a total of 134 incidental findings. Incidental findings within the head and neck (33.5% of all) excluding the thyroid were most common: 35% incidental findings were concerning for malignancy; of these, 25.5% were malignant with further workup. Recommendations were given by the head and neck radiologist on 72 (53.7%) findings: 74.5% of potentially malignant findings and 42.5% of benign findings had recommendations for follow-up. Significantly more patients with findings described as malignant were given recommendations for follow-up ( P = .0004). Conclusion: Incidental findings on FDG-PET/CT are present in more than one-third of patients with head and neck cancer. More than one-third of incidental findings were concerning for malignancy. This study illustrates how the incidental findings discovered on FDG PET/CT frequently necessitate additional evaluations unrelated to the index head and neck cancer. The impact of these additional assessments on the cost and quality of health care warrants future evaluation.